Novel hub genes and regulatory network related to ferroptosis in tetralogy of Fallot - Wang, Yu; Yang, Junjie; Lu, Jieru; Wang, Qingjie; Wang, Jian; Zhao, Jianyuan; Huang, Yuqiang; Sun, Kun (Frontiers in Pediatrics, 2023)
Ferroptosis is a newly discovered type of cell death mainly triggered by uncontrolled lipid peroxidation and it could potentially have a significant impact on the development and progression of Tetralogy of Fallot (TOF). Our project aims to identify and validate potential genes related to ferroptosis in TOF.We obtained sequencing data of Tetralogy of Fallot from the GEO database and ferroptosis-related genes from the ferroptosis database. We employed bioinformatics methods to analyze the differentially expressed mRNAs (DEmRNAs) and microRNAs (DEmiRs) between the normal control group and TOF group, and identify DEmRNAs related to ferroptosis. Protein-protein interaction (PPI) analysis was conducted to screen hub genes. Furthermore, a miRNA-mRNA-TF co-regulatory network was constructed utilizing prediction software. The expression of hub genes was further validated through qRT-PCR.After conducting the differential gene analysis, we observed that in Tetralogy of Fallot, there were 41 up-regulated mRNAs and 3 down-regulated mRNAs associated with ferroptosis genes. Further GO/KEGG analysis revealed that these genes were primarily involved in molecular functions and biological processes related to chemical stress, oxidative stress, cellular response to starvation, response to nutrient levels, cellular response to external stimulus, and cellular response to extracellular stimulus. Furthermore, we constructed a miRNA-mRNA-TF co-regulatory network. qRT-PCR analysis of the right ventricular tissues from human cases showed an upregulation in the mRNA levels of KEAP1 and SQSTM1. Our bioinformatics analysis successfully identified 44 potential genes that are associated with ferroptosis in Tetralogy of Fallot. This finding significantly contributes to our understanding of the molecular mechanisms underlying the development of Tetralogy of Fallot. Moreover, these findings have the potential to open new avenues for the development of innovative therapeutic approaches for the treatment of this condition.